Implementasi Aplikasi Finsense AI Sebagai Sarana Transformasi Digital Manajemen Keuangan Dan Mitigasi Risiko UMKM Di Kelurahan Batu Besar, Kota Batam - Rica Fitri Susanti UE; Andi Hidayatul Fadlilah; Fitri Mai Happy; Citra Apriana Ekasari; Widya Dwi Handayani; M Alfi Junaedi; Mohamad Hisam; Andi Sri Adinda Wulandari Adzan; Dewi Permata Sari (CV. Aksara Global Akademia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Kelurahan Batu Besar, Batam City, play a crucial role in the local economy. However, most of the business owners still manage their business finances manually. This condition leaves MSME actors vulnerable to cash flow uncertainty, difficulties in making long-term financial decisions, and limited access to assistance programs and business capital funding. This community service activity aims to implement the FinSense AI application as a means of digital financial management transformation for MSMEs in RW 08, Kelurahan Batu Besar. The implementation method was carried out from June 6, 2026, to July 4, 2026, through five stages, namely: (1) Preparation; (2) Socialization & Education; (3) Technical Training; (4) Intensive Mentoring; and (5) Evaluation. The results of the activity showed a significant increase in digital literacy and adoption, marked by an increase in the number of FinSense AI application users from 6 to 34 users. This application helps participants understand the financial health condition of their business and project financial feasibility. This activity concludes that the intervention of artificial intelligence technology is an effective step in boosting capacity and mitigating risks for MSMEs at the Kelurahan level.